Sluggish Cognitive Tempo in Adolescents with and without ADHD: Differentiation from Adolescent-reported ADHD Inattention and Unique Associations with Internalizing Domains - Becker, Stephen P. (J Abnorm Child Psychol, 2020)
A growing number of studies support the internal and external validity of youth self-reported sluggish cognitive tempo (SCT) symptoms. However, no study has examined SCT in adolescents without ADHD, examined whether adolescent self-reported SCT is distinct from adolescent self-reported ADHD inattention (ADHD-IN), or evaluated whether links between SCT and internalizing problems differ for adolescents with or without ADHD. The present study is the first to (1) determine the convergent and discriminant validity of self-reported SCT and ADHD-IN symptoms in both adolescents with and without ADHD, (2) test the invariance of SCT and ADHD-IN symptoms across ADHD and comparison groups, (3) examine SCT as uniquely related to a range of internalizing-relevant domains, and (4) evaluate if the association between SCT with internalizing correlates differs for adolescents with or without ADHD. Participants were adolescents (M(age)=13 years) with (n=162) and without (n=140) ADHD. Adolescents and parents completed measures of internalizing symptoms and emotion dysregulation; adolescents completed measures of rumination and suicidal ideation. Analyses indicated that 13 of the 15 SCT items demonstrated convergent and discriminant validity from ADHD-IN, and SCT and ADHD-IN demonstrated invariance across the ADHD and comparison groups and across sex. SCT, but not ADHD-IN, was uniquely associated with greater adolescent-reported internalizing symptoms and suicidal ideation. Both SCT and ADHD-IN were uniquely associated with adolescent-reported emotion dysregulation and parent-reported internalizing symptoms. Only ADHD-IN was uniquely associated with parent-reported emotion dysregulation. Findings support the differentiation of adolescent-reported SCT and ADHD-IN and demonstrate associations between SCT and increased internalizing problems in adolescents with and without ADHD.